Frequency of white matter hyperintensities on MRI in patients with migraine - Aqeela; Nawaz, Khurram Haq; Saeed, Sania; Khan, Tariq; Rehman, Wali (International Journal of Pathology, 2026)
Background: Migraine is a common neurological disorder characterized by recurrent headaches that significantly affect quality of life and daily functioning. Brain magnetic resonance imaging (MRI) often demonstrates white matter hyperintensities (WMHs), but their clinical significance remains uncertain. Therefore, this study was conducted to determine the frequency and radiological characteristics of WMHs on MRI in patients with migraine.Methods: This descriptive cross-sectional study was conducted at Pak Emirates Military Hospital, Rawalpindi. A total of 400 patients aged 18–60 years with migraine diagnosed according to the International Classification of Headache Disorders, 3rd edition (ICHD-3), were included through non-probability consecutive sampling. Brain MRI was performed using T2-weighted and fluid-attenuated inversion recovery (FLAIR) sequences. Associations were evaluated using the Chi-square test, and multivariable binary logistic regression analysis was performed to identify independent predictors of WMHs. Data were analyzed using SPSS version 28.Results: WMHs were significantly more frequent in patients aged >40 years (p<0.001), those with chronic migraine (p=0.01), and those with a migraine duration >5 years (p=0.003). Binary logistic regression demonstrated that age >40 years, chronic migraine, and migraine duration >5 years were independent predictors of WMHs, whereas gender, migraine aura, hypertension, and diabetes mellitus were not independently associated.Conclusion: WMHs are common MRI findings in patients with migraine, particularly in older patients and those with chronic or long-standing disease. Most lesions are small, mild, and predominantly involve the frontal and deep white matter. These findings may improve the interpretation of MRI findings and contribute to a better understanding of migraine-related brain changes.